2002
DOI: 10.1111/j.1348-0421.2002.tb02746.x
|View full text |Cite
|
Sign up to set email alerts
|

Serological Evidence of Transmission of Human Influenza A and B Viruses to Caspian Seals (Phoca caspica)

Abstract: Seroepidemiological surveillance of influenza in Caspian seals (Phoca caspica) was conducted. Antibodies to influenza A virus were detected in 54% (7/13), 57% (4/7), 40% (6/15) and 26% (11/42) of the serum samples collected in 1993, 1997, 1998 and 2000 by enzyme‐linked immunosorbent assay (ELISA). In an hemagglutination‐inhibition (HI) test using H1‐H15 reference influenza A viruses as antigens, more than half of the examined ELISA‐positive sera reacted with an H3N2 prototype strain A/Aichi/2/68. These sera we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
1
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 19 publications
3
52
1
4
Order By: Relevance
“…Anti-influenza virus Abs in serum obtained from seven young and 11 elderly individuals before and 3 mo after vaccination were measured by ELISA as previously described (27), with some modifications. Briefly, 96-well microtiter plates (ICN Biomedicals, Aurora, OH) were coated overnight at 4°C with lysates of influenza virus (A/New Caledonia, A/Panama, and B/Hong Kong) in coating buffer at 1 g/ml.…”
Section: Determination Of Anti-influenza Virus Abs In Serummentioning
confidence: 99%
“…Anti-influenza virus Abs in serum obtained from seven young and 11 elderly individuals before and 3 mo after vaccination were measured by ELISA as previously described (27), with some modifications. Briefly, 96-well microtiter plates (ICN Biomedicals, Aurora, OH) were coated overnight at 4°C with lysates of influenza virus (A/New Caledonia, A/Panama, and B/Hong Kong) in coating buffer at 1 g/ml.…”
Section: Determination Of Anti-influenza Virus Abs In Serummentioning
confidence: 99%
“…Therefore, it is possible that ELISA might show a positive for the virus without the subtype being identifiable by HI test. Previous serological studies on influenza A virus infection have shown that the same sample can test positive by ELISA but negative by HI test [22][23][24]. In this study, antibodies to H3 and H6 subtypes of influenza A virus were detected from sera collected from Kuril harbor seals at Nosappu.…”
Section: Discussionmentioning
confidence: 80%
“…Enzyme-linked immunosorbent assay (ELISA): ELISA was performed according to the modified procedure described previously [16,24]. Purified A/Aichi/2/68 (H3N2) virus was disrupted in 0.5 M Tris pH 7.8 containing 0.5% Triton X-100 and 0.6 M KCl and diluted to 2 µg/ml in phosphate-buffered saline (PBS).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Influenza B viruses isolated from seals and pigs were likely acquired by reverse zoonotic events (Bodewes et al, 2013;Ohishi et al, 2002;Osterhaus et al, 2000;Ran et al, 2015). Although several studies have described infection of ferrets with influenza type B viruses (Huang et al, 2014;Kim et al, 2009), we were interested in understanding at the cellular level how appropriate the ferret model is for the study of human influenza B viruses.…”
Section: Introductionmentioning
confidence: 99%